Public-Private Sector Wage Differentials in Australia - Stéphane Mahuteau; Kostas G. Mavromaras; Sue Richardson; Rong Zhu (Institute of Labor Economics (IZA), 2017)
This paper examines wage differentials between public sector and private sector workers in Australia. After controlling for observed characteristics and individual fixed effects, we show that on average workers in the public sector earn about 5.1% percent more hourly wages than those in the private sector. The wage premium is slightly higher for females than males. Using a panel data quantile regression model with fixed effects, we show that the positive wage effects of public sector employment are heterogeneous, with comparatively larger impact at the lower end of the wage distribution than at other parts. We also find evidence of heterogeneity in the public sector wage premiums by qualification, time period, occupation and state/territory.
Keywords: J31; J45; 330; public sector; private sector; wage gap